An Aptamer-Array-Based Sample-to-Answer Biosensor for Ochratoxin A Detection via Fluorescence Resonance Energy Transfer - Yongning Li (MDPI AG, 2021)
Food toxins are a hidden threat that can cause cancer and tremendously impact human health. Therefore, the detection of food toxins in a timely manner with high sensitivity is of paramount importance for public health and food safety. However, the current detection methods are relatively time-consuming and not practical for field tests. In the present work, we developed a novel aptamer-chip-based sample-to-answer biosensor (ACSB) for ochratoxin A (OTA) detection via fluorescence resonance energy transfer (FRET). In this system, a cyanine 3 (Cy3)-labeled OTA-specific biotinylated aptamer was immobilized on an epoxy-coated chip via streptavidin-biotin binding. A complementary DNA strand to OTA aptamer at the 3′-end was labeled with a black hole quencher 2 (BHQ2) to quench Cy3 fluorescence when in proximity. In the presence of OTA, the Cy3-labeled OTA aptamer bound specifically to OTA and led to the physical separation of Cy3 and BHQ2, which resulted in an increase of fluorescence signal. The limit of detection (LOD) of this ACSB for OTA was 0.005 ng/mL with a linearity range of 0.01–10 ng/mL. The cross-reactivity of ACSB against other mycotoxins, ochratoxin B (OTB), aflatoxin B1 (AFB1), zearalenone (ZEA), or deoxynilvalenol (DON), was less than 0.01%. In addition, this system could accurately detect OTA in rice samples spiked with OTA, and the mean recovery rate of the spiked-in OTA reached 91%, with a coefficient of variation (CV) of 8.57–9.89%. Collectively, the ACSB may represent a rapid, accurate, and easy-to-use platform for OTA detection with high sensitivity and specificity.